Avaliação de níveis e fontes de proteína na alimentação de leitões na fase inicial de crescimento - Junqueira, Otto Mack [UNESP]; Silz, Liliam Zambrana Toledo [UNESP]; Araújo, Lúcio Francelino [UNESP]; Pereira, Adriana Aparecida [UNESP]; De Laurentiz, Antônio Carlos [UNESP]; Filardi, Rosemeire Da Silva [UNESP] (My University, 2008)
An experiment was conducted to compare different levels and sources of protein on performance, intestinal morphology and pancreas weight/carcass weight ratio in the diets of piglets from 36 to 70 days old. A total of 96 piglets was allotted to a randomized experimental block design in six diets, with different levels and protein sources, four replicates of four animals per experimental unit. The levels and the protein sources evaluated were: dry skim milk (8.80 and 12.00%), isolated soybean protein (3.20 and 4.50%), fish meal (5.00%) and dry yeast (10.00%). The diets were isoenergetics and isoproteics. The diets did not affect weight gain and feed conversion of the animals, however, the pigs that were fed diet with dry skim milk showed higher feed intake from 56 to 63 days old. There was no effect of protein sources on villus height, crypt depth and pancreas weight/carcass weight ratio. The levels and protein sources in the diet did not affect performance, intestinal morphology and pancreas weight/carcass ratio of the piglets from 36 to 70 days old. © 2008 Sociedade Brasileira de Zootecnia.
Evaluation of levels and protein sources in diets of piglets in the initial growth phase
Keywords: Dry skim milk; Dry yeast; Fish meal; Intestinal morphology; Isolated soybean protein; Performance